Determination of different types of phreatomagmatic breccia facies in the Islay mine diatrem - Chuquitoma Huamani, Julio César (2023)
The objective of this study is to characterize the composition of a diatreme breccia by means of a lithological description in order to characterize the mineralized economic replacement levels of the linked stratum type (mantles/bodies) related to Zn – Pb – Ag mineralization, in the zones favorable areas located at the edges of the diatreme breccia, in the lower levels of the Islay mine in order to elevate the mineral deposit from small mining to a category of medium mining.From the analysis it was determined that the Islay mine is associated with a diatreme of phreatomagmatic origin, composed of different lithofacies of breccias, tuffaceous levels, tectonic breccias and local fractures that could be cemented by economic mineralization, by identifying the different facies that make up the phreatomagmatic gap we could determine the presence of economically exploitable mineralized bodies and mantles.